2014
DOI: 10.1038/nphys2961
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage magnetic-field-tuned superconductor–insulator transition in underdoped La2−xSrxCuO4

Abstract: In the underdoped pseudogap regime of cuprate superconductors, the normal state is commonly probed by applying a magnetic field (H). However, the nature of the H-induced resistive state has been the subject of a long-term debate, and clear evidence for a zero-temperature (T = 0) H-tuned superconductor-insulator transition (SIT) has proved elusive. Here we report magnetoresistance measurements in underdoped La 2−x Sr x CuO 4 , providing striking evidence for quantum critical behavior of the resistivity -the sig… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
102
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 45 publications
16
102
0
Order By: Relevance
“…Our observation shows similar behavior of SI transition in ultrathin fi lms of bismuth, [ 23 ] superconducting LaTiO 3 /SrTiO 3 interfaces, [ 24,25 ] and underdoped La 2-x Sr x CuO 4 (LSCO), [26][27][28] where there is a critical magnetic fi eld that separates the superconducting state from the insulating state. To see if the "resistance drop" is representative of superconductivity found in BiOCl MP, we also measured the magnetoresistance of the sample (Figure 4 b) and ρ as a function of the excitation current I (Figure 4 c) at different temperatures.…”
Section: Doi: 101002/admi201500194supporting
confidence: 76%
“…Our observation shows similar behavior of SI transition in ultrathin fi lms of bismuth, [ 23 ] superconducting LaTiO 3 /SrTiO 3 interfaces, [ 24,25 ] and underdoped La 2-x Sr x CuO 4 (LSCO), [26][27][28] where there is a critical magnetic fi eld that separates the superconducting state from the insulating state. To see if the "resistance drop" is representative of superconductivity found in BiOCl MP, we also measured the magnetoresistance of the sample (Figure 4 b) and ρ as a function of the excitation current I (Figure 4 c) at different temperatures.…”
Section: Doi: 101002/admi201500194supporting
confidence: 76%
“…We can only conjecture that disorder, which is present even in the best YBCO single crystals [37], plays a role. In particular, for two-dimensional systems in the presence of disorder, it has been shown that rare regions with anomalously high H c2 values become Josephsoncoupled at very low T [38][39][40][41]. This gives rises to two stages in the superconducting-to-normal transitions measured by resistivity vs. field [38][39][40][41].…”
Section: Vortex Melting Transitionmentioning
confidence: 99%
“…In previous reports on SITs and SMTs, the magnetic resistance isotherms cross in one or two points, which are considered as quantum criticality. [14][15][16][17][18][19][20] However, in recent work on 2D superconducting Ga films 22 , the similar continuous line of SMT "critical" points and the dynamical critical exponent divergence were detected, which experimentally revealed quantum Griffiths singularity of SMTs in Ga films. 7,21,22 We then analyze our data referring to the finite size analysis method 22 (See supplemental information for details).…”
Section: Textmentioning
confidence: 99%
“…[14][15][16][17][18][19][20] We note that the high critical magnetic field in low temperature regime has been observed in heavy Fermion superconductors 31 and organic superconductors 32 . The mechanism was interpreted as Fulde-Ferrell-Larkin-Ovchinnikov (FFLO) state 33 .…”
Section: Textmentioning
confidence: 99%